Exciton absorption spectrum of Cs₄PbCl₆ thin films - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N.; Kovalenko, V.V. (Functional Materials, 2015)
Absorption spectrum of Cs₄PbCl₆ thin films was studied in the spectral range of 2-6 eV within the temperature interval 90-500 K. Localization of low-frequency excitonic states in sublattice of the compound containing Pb²⁺ ions was established. Excitons have intermediate bond and two-dimensional (2D) nature.